THE EVALUATION OF BERMASA VILLAGE PROGRAM ON PLANNING AND BUDGETING FOR VILLAGE DEVELOPMENT IN MANDIRI VILLAGE, BANTAN SUB-DISTRICT - Pebiona, Gressila; Fiddin, Fachroh (Petra Christian University, 2023)
This research aims to determine the evaluation of the BERMASA Village Program in planning and budgeting, comparisons between Mandiri villages in Bantan sub-district, and the obstacles faced by village governments in Mandiri Village, Bantan sub-district, in formulating planning and budgeting for the Village Based Program. This is a qualitative descriptive study that uses primary and secondary data. The informants in this research consist of the Village Head, Village Secretary, Village Treasurer, Chair of the Village Consultative Body, and Chair of the Development Implementation Team. The research data was obtained from four Mandiri villages, namely Bantan Tengah, Selatbaru, Berancah, and Pasiran. The data collection techniques used in this study were interviews, observations, and documentation. The research findings show that the evaluation of the BERMASA Village Program in planning and budgeting for village development in Mandiri Village, Bantan sub-district, is in accordance with the Regulation of the Bengkalis Regent No. 74 of 2021 concerning Guidelines for Financial Aid Management, which specifically applies to the BERMASA Village Program, and the Decree of the Head of the Department of Community Empowerment and Village Affairs of Bengkalis Regency No. 073/KPTS/XI/2022 concerning Technical Guidelines for the Use of Financial Assistance, which specifically applies to the BERMASA Village Program. The village government always involves the community in the planning and budgeting process, and decision-making is always based on a deliberative system from the hamlet to the village level. The comparison between Mandiri villages for the received budget funds of IDR 1,000,000,000 consists of mandatory and optional activities. However, the obstacles faced by the village government are related to the implementation of determining activities and unforeseen conditions.